PENGARUH KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP KINERJA AUDITOR INTERNAL BANK BUMN DI KANWIL PALEMBANG - Nurmawati Oktaria; Rina Tjandrakirana (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2012)
This research is devoted to assessing the performance of internal auditors in banking. The deteriorating performance makes a banking becomes unhealthy or not in accordance with the standards, then the necessary internal controls conducted by the bank's internal audit. And in assessing the professionalism of internal auditors, viewed from the aspect of competence and independence of auditors. Population of this study is the custom auditors in Palembang Region by taking 21 auditors for sample. Data collection was done by using enquete with likert scale. Data analysis was conducted by using multiple correlation and regression method at significance 98,2%. Types of data collected, obtained from the questionnaire answers are filled by internal auditors who were respondents in the form of literary study and previous studies. This study aims to measure the influence of competence and independence of the auditor's performance and level of correlation between these variables. The proposal is expected to become the company's view in selecting an auditor who has performed well. Keyword : competence, independence, performance